Pressões e protagonismos na trajetória de trabalhadores em Marechal Cândido Rondon–PR (2000-2017) - Lagos, Saionara (2018)
This dissertation deals with the problematization of the possible meanings expressed in the disposition of workers when they put the demand of work in front of the pressures and limits in which they are inserted, proposing a reflection on the possibilities of work in the city of Marechal Cândido Rondon between the years of 2000 -2017, observing how these labor relations modify the ways of living and producing the city. For this purpose, we treat sources in a way that considers them constructions based on interests, which does not minimize their wealth, but instigates to problematize how in a same historical moment the expressed concerns can be divergent or even contradictory. The research was built through the analysis of sources such as interviews with workers and the local newspaper "O Presente", in which we researched matters that deal with the presence of these workers in the city. In the same newspaper, I analyze search-for-work ads in an attempt to access how workers have engaged in such relationships by targeting their ads to certain vacancies. In addition to making use of employee registration forms in the National Employment System (SINE), in order to understand how the process of finding workers by this agency was an intermediary between them and the employers. Analyzing the work of workers in the 21st century allows us to perceive spaces of confrontation in which these subjects decide how and where to work from the way they live or long to live.